2021
DOI: 10.1080/19490976.2021.1874740
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-derived short-chain fatty acids do not interfere with SARS-CoV-2 infection of human colonic samples

Abstract: Microbiota-derived molecules called short-chain fatty acids (SCFAs) play a key role in the maintenance of the intestinal barrier and regulation of immune response during infectious conditions. Recent reports indicate that SARS-CoV-2 infection changes microbiota and SCFAs production. However, the relevance of this effect is unknown. In this study, we used human intestinal biopsies and intestinal epithelial cells to investigate the impact of SCFAs in the infection by SARS-CoV-2. SCFAs did not change the entry or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
3
31
0
4
Order By: Relevance
“…A recent study found that SCFAs do not interfere with SARS-CoV-2 infection in the intestine. 31 Although the SCFA concentrations used in that study were much lower than those used in our experiment, the effects of SCFAs on the airway and intestine may vary.…”
Section: Discussionmentioning
confidence: 70%
“…A recent study found that SCFAs do not interfere with SARS-CoV-2 infection in the intestine. 31 Although the SCFA concentrations used in that study were much lower than those used in our experiment, the effects of SCFAs on the airway and intestine may vary.…”
Section: Discussionmentioning
confidence: 70%
“…Butyrate (one of the key SCFAs)-producing bacterium is significantly reduced during COVID-19 infection [ 27 , 29 , 31 , 35 , 53 ]. The resulting reduction of butyrate production in the gut may be linked to a pro-inflammatory state [ 54 ], thus increasing susceptibility to pulmonary viral infections, including COVID-19 [ 55 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting reduction of butyrate production in the gut may be linked to a pro-inflammatory state [ 54 ], thus increasing susceptibility to pulmonary viral infections, including COVID-19 [ 55 57 ]. Although evidence suggests that SCFA does not interfere with COVID-19 infection in the intestine [ 53 ], a reduction in SCFA may promote a systemic pro-inflammatory state in both macaques [ 52 ] and humans [ 58 ]. In support of this, dietary interventions may alter the composition of airway and intestinal microbiota, which may potentially affect the clinical course of COVID-19 infection by modulating systemic immune responses [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients showed significant dysbiosis of the fecal microbiome, which was characterized by an enrichment of opportunistic pathogens and a depletion of beneficial commensals [ 19 ]. Numerous experimental and clinical observations suggested that the gut microbiota plays a key role in the pathogenesis of sepsis and acute respiratory distress syndrome, suggesting that SARS-CoV2 might also have an impact on the gut microbiota and vice-versa [ 41 , 42 , 43 ]. Our results showed that serum and fecal total IgA levels were substantially higher in the COVID-19 IgAN case than in healthy controls, as were the levels of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%